Passive Suicide Ideation: An Indicator of Risk Among Older Adults Seeking Aging Services?. (8th April 2014) - Van Orden, Kimberly A.; O'Riley, Alisa A.; Simning, Adam; Podgorski, Carol; Richardson, Thomas M.; Conwell, Yeates
Abstract: Objectives: This study examines patterns of endorsements of active suicide ideation (SI), passive SI (synonymous with death ideation), and psychological distress (i.e., depressive and anxious symptomatology) in a sample of vulnerable older adults. Methods: Data were collected via in-home interviews with aging services care management clients aged 60 years and older ( n = 377). The Paykel scale for suicide measured the most severe level of suicidality over the past year, and the ninth item of the Patient Health Questionnaire (PHQ-9) measured current passive/active SI. The remaining items from the PHQ (i.e., PHQ-8) and the Goldberg Anxiety scale measured distress. Results: Latent class analysis revealed a four-class model: a group with mild distress and no active SI, a group with high distress and no ideation, a group with mild distress and both passive and active SI, and a group with high distress and both passive and active SI. Discussion: Results indicate that passive SI rarely presents in vulnerable older adults in the absence of significant risk factors for suicide (i.e., psychological distress or active SI). Thus, the desire for death and the belief that life is not worth living do not appear to be normative in late life.